Síntese de zeólitas e argilas ácidas pilarizadas a partir de matérias primas naturais - Bieseki, Lindiane (2012)
Structural changes in waste for zeolites synthesis are subject of many studies carried out in the synthesis of molecular sieves. These materials are named molecular sieves because they have well defined pore sizes and they have the capacity of select molecules by its size. In this work, it was studied the synthesis processes of two types of molecular sieves: pillared acid clays using as starting material one natural montmorillonite clay and the synthesis of zeolites from a silico-aluminous residue. This residue is a byproduct of the extraction of lithium -spodumene. The preparation of pillared acid clays was performed in two steps: 1° acid treatment of clay samples (time and temperature studies) and 2°pilarization of them with Al13 (Keggin ion). The temperature and acid concentration affect the removal of cations in the structure and porosity of the material obtained. The analysis of X-ray diffraction (XRD) and infrared spectroscopy (IR), showed that increasing the severity of the acid treatment compromises the structural material. Also the pore size distribution is approximately uniform. Despite presenting a structural disorganization, the samples were pillared. As evidenced by XRD increasing the basal spacing, specific area and uniform porosity by adsorption of N2. Regarding the microporous molecular sieves were synthesized zeolites A and NaP1 from a silico-aluminous residue, a byproduct of extracting lithium. The temperature and time of agitation during the synthesis were the most important factors for obtaining zeolite A. The aging of the gel and the highest crystallization time promoted the formation of zeolite NaP1 using a Si / Al ratio = 3.2